ESPORTS SEBAGAI ALAT DIPLOMASI PUBLIK OLEH TIONGKOK - Farrand, Andi Almer (Fakultas Ilmu Sosial dan Ilmu Politik Universitas Riau, 2023)
Similar to traditional sports, electronic sports (eSports) has the potential to function as a soft power asset in a country's Public Diplomacy (PD) efforts due to its widespread international broadcasts. Recent discussions on sports diplomacy have highlighted how states can enhance their global image, much like players and teams that achieve success in international competitions. However, eSports brings an added dimension to PD by potentially conveying cultural and political values through artistic video game content. Despite this, there has been a dearth of research into the utilization of eSports in Public Diplomacy, which is the focus of this thesis. The Research employs PD theories, including the Domestic Dimension concept, which elucidates how non-state actors can serve as both recipients and independent public dipl omats in the realm of Public Diplomacy. Key concepts like soft power, smart power, and strategic narrative aid in comprehending how eSports can be harnessed as a soft power asset, while the concept of fragmented authoritarianism is used as a framework to challenge the conventional monolithic perspective on China's role in PD. The findings of this research reveal that numerous state and non-state actors in China have already integrated eSports into their PD endeavors. Nonetheless, the onset of the pandemic and the introduction of the aforementioned restrictions have impeded these efforts. State actors, such as the Ministry of Culture, have incorporated eSports into cultural diplomacy by categorizing it as a facet of China's digital culture, subsequently integrating it into existing initiatives like the Belt and Road Initiative. Non-state actors, such as Tencent and city governments, often support state actors by organizing globally broadcasted events. Furthermore, Tencent's ownership of numerous international and local game developers is directed towards creating eSports titles that depict Chinese culture and China in a favorable light. Keywords: eSports, Public Diplomacy, China, Soft Power, Non-state actors